2020
DOI: 10.1099/jgv.0.001410
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence, genetic diversity and a potentially novel genotype of Sapelovirus A (Picornaviridae) in enteric and respiratory samples in Hungarian swine farms

Abstract: All of the known porcine sapeloviruses (PSVs) currently belong to a single genotype in the genus Sapelovirus (family Picornaviridae). Here, the complete genome of a second, possibly recombinant, genotype of PSV strain SZ1M-F/PSV/HUN2013 (MN807752) from a faecal sample of a paraplegic pig in Hungary was characterized using viral metagenomics and RT-PCR. This sapelovirus strain showed only 64 % nucleotide identity in the VP1 region to its closest PSV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…Our results indicate that PSV is largely widespread especially among younger animals confirming previous findings observed in Korea [15] Spain [14], the Czech Republic [11], and Hungary [9]. In general, circulation in older animals is not detected or occurs less frequently (Spain and the Czech Republic) [11,14].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results indicate that PSV is largely widespread especially among younger animals confirming previous findings observed in Korea [15] Spain [14], the Czech Republic [11], and Hungary [9]. In general, circulation in older animals is not detected or occurs less frequently (Spain and the Czech Republic) [11,14].…”
Section: Discussionsupporting
confidence: 89%
“…The occurrence of PSV was frequent, the virus was detected on the three farms with 97-100% positive pools in young growers. Besides the limited number of farms investigated, the presence of PSV was apparently higher than reported in previous studies in both India and Spain, [9,14] but similar to the results reported in Hungary [9]. These data confirm a wide circulation of PSV worldwide but with some geographical differences that may be linked to the epidemiology of infections or farm management procedures.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Since PSV was rst reported in the UK in 1958 [6], it has been identi ed in many countries, including Canada, Japan, Australia, Brazil, Spain and Korea, and China and other countries worldwide [5,[7][8][9][10][11][12]. PSV infection rates in pigs have been investigated globally, with prevalence rates ranging from 7.1% in India [13] to 71.0% in Hungary [14]. PSV infections have been associated with a wide spectrum of symptoms ranging from asymptomatic infection to acute fatal encephalomyelitis, reproductive disorders, diarrhoea and pneumonia [12,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%